2020
DOI: 10.2967/jnumed.119.228304
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Imaging of Cardiovascular Device Infection: Targeting the Bacteria or the Host–Pathogen Immune Response?

Abstract: Learning Objectives: On successful completion of this activity, participants should be able to (1) understand the role of 18 F-FDG PET/CT for diagnosis of cardiovascular device infection, as a functional imaging tool for assessing the overall host-pathogen immune response in infection; (2) learn about the strengths and limitations of bacteria-targeting radiotracers for infection imaging, including those based on substances of bacterial maltodextrin transporters, bacterial thymidine kinase, antibiotics, antimic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 68 publications
0
11
0
Order By: Relevance
“…Zhao et al found that, SARS-CoV-2 infects human respiratory epithelial cells through the interaction of S-protein and human ACE2 [ 3 ]. Later, Markus Hoffmann et al released a related study on BioRxiv , showing that SARS-CoV-2 infects through the same ACE2 receptor as does SARS coronavirus, and employs the cell protease TMPRSS2 used for SARS-CoV-2 [ 4 , 5 ]. Since ACE2 is the only entrance through which SARS-CoV-2 invades cells, it is particularly important to develop clinical drugs that target and inhibit viral entry as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…Zhao et al found that, SARS-CoV-2 infects human respiratory epithelial cells through the interaction of S-protein and human ACE2 [ 3 ]. Later, Markus Hoffmann et al released a related study on BioRxiv , showing that SARS-CoV-2 infects through the same ACE2 receptor as does SARS coronavirus, and employs the cell protease TMPRSS2 used for SARS-CoV-2 [ 4 , 5 ]. Since ACE2 is the only entrance through which SARS-CoV-2 invades cells, it is particularly important to develop clinical drugs that target and inhibit viral entry as early as possible.…”
Section: Introductionmentioning
confidence: 99%
“…After a careful evaluation, 0.50-Gd 2 O 3 @MSN (herein after referred as Gd 2 O 3 @MSN), was chosen for modification with NH 2 -maltodextrins (NH 2 -Malt) and further experiments. To decorate the surfaces of Gd 2 O 3 @MSN NPs for effective bacterial targeting, NH 2 -Malt with high specificity and sensitivity toward bacteria by bacteria-specific maltodextrin transporter, , was synthesized (Figure S2). After NH 2 -Malt was conjugated to Gd 2 O 3 @MSN NPs via a facile amidation reaction that leverages the abounding amino and carboxyl groups in NH 2 -Malt to Gd 2 O 3 @MSN, respectively, there were no significant morphological differences between Gd 2 O 3 @MSN and Gd 2 O 3 @MSN-Malt NPs (Figure D).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Maltodextrins, including maltotriose, maltotetraose, maltohexaose, and maltoheptaose, have gained extensive attention because of their high sensitivity and specificity toward a broad strain of bacteria. As a major source of glucose for bacteria, maltodextrins can be robustly internalized via the bacteria-specific maltodextrin transporter. , After conjugation with fluorescence molecules or a PET tracer, maltodextrin can provide an unprecedented sensitivity and specificity in the imaging of bacterial infections in vivo. For example, maltohexaose-based fluorescence probes can be internalized by both Gram-positive and Gram-negative bacteria (e.g., E. coli , S. aureus , P. aeruginosa , and B. subtilis ) under aerobic and anerobic fermentative conditions .…”
Section: Introductionmentioning
confidence: 99%
“…Published data suggested that visual grading score and early imaging prior to antimicrobial treatment may further improve the diagnostic accuracy of 18F-FDG PET/CT [45]. Hopefully in the future, novel diagnostic scores may help to differentiate foreign body reactions and bacterial targeting tracers will be introduced to clinical care [46]. Some of the studies included are classified as low quality according to GRADE criteria.…”
Section: Discussionmentioning
confidence: 99%